In mathematics, Nesbitt's inequality, named after Alfred Nesbitt, states that for positive real numbers a, b and c,
a | |
b+c |
+
b | |
a+c |
+
c | |
a+b |
\geq
3 | |
2 |
,
a=b=c
There is no corresponding upper bound as any of the 3 fractions in the inequality can be made arbitrarily large.
It is the three-variable case of the rather more difficult Shapiro inequality, and was published at least 50 years earlier.
(a+b),(b+c),(c+a)
(a+b)+(a+c)+(b+c) | |
3 |
\geq
3 | ||||||||||
|
.
((a+b)+(a+c)+(b+c))\left( | 1 |
a+b |
+
1 | |
a+c |
+
1 | |
b+c |
\right)\geq9,
2 | a+b+c |
b+c |
+2
a+b+c | |
a+c |
+2
a+b+c | |
a+b |
\geq9
Supposing
a\geb\gec
1 | |
b+c |
\ge
1 | |
a+c |
\ge
1 | |
a+b |
.
\vec{x}=(a,b,c)
\vec{y}=\left(
1 | |
b+c |
,
1 | |
a+c |
,
1 | |
a+b |
\right)
\vecy1
\vecy2
\vecy
\vec{x} ⋅ \vec{y}\ge\vec{x} ⋅ \vecy1
\vec{x} ⋅ \vec{y}\ge\vec{x} ⋅ \vecy2
Addition then yields Nesbitt's inequality.
The following identity is true for all
a,b,c:
a | |
b+c |
+
b | |
a+c |
+
c | |
a+b |
=
3 | |
2 |
+
1 | \left( | |
2 |
(a-b)2 | |
(a+c)(b+c) |
+
(a-c)2 | |
(a+b)(b+c) |
+
(b-c)2 | |
(a+b)(a+c) |
\right).
3/2
Note: every rational inequality can be demonstrated by transforming it to the appropriate sum-of-squares identity—see Hilbert's seventeenth problem.
Invoking the Cauchy–Schwarz inequality on the vectors
\displaystyle\left\langle\sqrt{a+b},\sqrt{b+c},\sqrt{c+a}\right\rangle,\left\langle | 1 |
\sqrt{a+b |
((b+c)+(a+c)+(a+b))\left( | 1 |
b+c |
+
1 | |
a+c |
+
1 | |
a+b |
\right)\geq9,
Let
x=a+b,y=b+c,z=c+a
x+z | |
y |
+
y+z | |
x |
+
x+y | |
z |
\geq6,
x | |
y |
+
z | |
y |
+
y | |
x |
+
z | |
x |
+
x | |
z |
+
y | |
z |
\geq6\sqrt[6]{
x | |
y |
⋅
z | |
y |
⋅
y | |
x |
⋅
z | |
x |
⋅
x | |
z |
⋅
y | |
z |
Substituting out the
x,y,z
a,b,c
2a+b+c | |
b+c |
+
a+b+2c | |
a+b |
+
a+2b+c | |
c+a |
\geq6
2a | |
b+c |
+
2c | |
a+b |
+
2b | |
a+c |
+3\geq6,
Titu's lemma, a direct consequence of the Cauchy–Schwarz inequality, states that for any sequence of
n
(xk)
n
(ak)
| |||||||||||
\displaystyle\sum | \geq | ||||||||||
k=1 |
| ||||||||||||||||
|
.
We use the lemma on
(xk)=(1,1,1)
(ak)=(b+c,a+c,a+b)
1 | |
b+c |
+
1 | |
c+a |
+
1 | |
a+b |
\geq
32 | |
2(a+b+c) |
,
a+b+c | |
b+c |
+
a+b+c | |
c+a |
+
a+b+c | |
a+b |
\geq
9 | |
2 |
a | |
b+c |
+
b | |
c+a |
+
c | |
a+b |
\geq
9 | |
2 |
-3=
3 | |
2 |
.
As the left side of the inequality is homogeneous, we may assume
a+b+c=1
x=a+b
y=b+c
z=c+a
1-x | |
x |
+
1-y | |
y |
+
1-z | |
z |
\ge
3 | |
2 |
1 | |
x |
+
1 | |
y |
+
1 | |
z |
\ge
9 | |
2 |
Let
S=a+b+c
f(x)= | x |
S-x |
[0,S]
\displaystyle
| |||||||||||
3 |
\geq
S/3 | |
S-S/3 |
.
a | |
b+c |
+
b | |
c+a |
+
c | |
a+b |
\geq
3 | |
2 |
.
By clearing denominators,
a | |
b+c |
+
b | |
a+c |
+
c | |
a+b |
\geq
3 | |
2 |
\iff2(a3+b3+c3)\geqab2+a2b+ac2+a2c+bc2+b2c.
x3+y3\geqxy2+x2y
(x,y)\in
2 | |
R | |
+ |
(x,y)=(a,b), (a,c),
(b,c)
As
x3+y3\geqxy2+x2y\iff(x-y)(x2-y2)\geq0